Child malnutrition in Toamasina hospital: the determining role of the socio economic conditions of the mother - Kasy, Emile; Ratsimbazafy, Arthur; Andriafanjanomenjanahary, Judicael; Andrianarivelo, Andry Maharo; Anissa, Van Cuong Miora; Randriamanantena, N. (International Journal Of Community Medicine And Public Health, 2019)
Background: The severe malnutrition is the background of infant mortality in Toamasina region. In spite of the efforts given to the care of those undernourished, this medical scourge always clamps down in national scale. A wider look shows that it is not only a health problem but also socio economic. Our study has as goal to detect the degree of influence of socio economic conditions of mothers about nutritional and weights condition of the childrenespecially in hospitals. Methods: We led a cross descriptive retrospective study based on hospitalized children records in Intensive Nutritional Recovery Center (INRC) of the University Hospital Center (UHC) of Toamasina during 2017. Results: 150 children have been included in the study. The average age of children is 11 months and there is no particular difference found concerning their gender. The breastfeeding was found in most of the case (90%). Concerning the mother, the average age is 21, 5. Those mothers were singles in 76.67% of the cases and practiced informal activities in 62% of the cases. We have deplored 3 deaths during our study period. Conclusions: The poor socio economic condition of the mothers influences considerably the risk to expose the children less than 5 years to the malnutrition. A combined action between health workers and economists is compulsory so as to get through this scourge.